Microporous Conjugated Polymers with Enhanced Emission in Immiscible Two‐Phase System in Response to Surfactants. Issue 1 (4th December 2013) - Kim, Shin‐Il; Jin, Young‐Jae; Lee, Wang‐Eun; Yu, Ri; Park, Sang‐Joon; Kim, Hyo‐Jin; Song, Kyu‐Ho; Kwak, Giseop
<x xml:space="preserve">Abstract</x> A microporous, conjugated polymer with a conformation‐variable stack structure is highly responsive to a change in the surface tension of water, either physicochemically or electronically. The polymer film and powder become readily wet with water by the addition of (bio)surfactants to reveal emission‐enhanced fluorescence, which are applied to saponin detection, image patterning and ink‐jet printing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>